المسؤولية الاجتماعية للمؤسسات الاقتصادية في ظل المبادرات الدولية - حمزة, فطيمة (جامعة الوادي - University of Eloued, 2023)
كانت المؤسسات تمارس نشاطاتها بكل حرية دون ان تأخذ في عين الاعتبار الاثار التي يمكن ان تخلفها وراءها جراء نشاطاتها سواء كان داخليا او خارجيا، لكن مع التطورات التي حدثت في جميع الجوانب وظهور ما يسمي باقتصاد المعرفة، بدأت تلك المؤسسات يتعدى اهتمامها الجانب الاقتصادي فقط بل بدأت تهتم بالجوانب الاجتماعية ليشمل البيئة التي تنشط فيها، لذلك ظهرت تقارير أخرى غير التقارير المالية الا وهي التقارير حول مسؤوليتها الاجتماعية والتي تعكس مساهمتها التي قامت بها اتجاه المجتمع باعتبارها أداة لتحقيق التنمية المستدامة. Institutions exercised their activities freely without taking into account the effects they might leave behind as a result of their activities whether internal or external, but with developments in all aspects and appearance The knowledge economy, these institutions began to outgrow their interest on the economic side Only On the contrary, she began to take an interest in the social aspects Therefore, other reports have emerged other than the financial reports, which are the reports on its social responsibility, which reflect its contribution to society as a tool to achieve sustainable development.
Social responsibility of economic institutions in the light of international initiatives
مقال
Keywords: مسؤلية اجتماعية ; مؤسسة اقتصادية ; تنمية مستدامة ; اقتصاد د; Social responsibility; economic enterprise; Sustainable development; international economy